Anti-Bullying Education Media Innovation through Local Culture-Based Bilingual Audio E-Comic for Elementary School Students - Umi Nahdhiah; Muhammad Aidi Noor Ihsan; Sijah Mariani; Aynin Mashfufah (Jurnal Ilmiah Sekolah Dasar, 2024)
Bullying is still rampant, especially at the elementary school level, which is crucial to overcome. This research aims to develop learning media in the form of e-comic with audio in two languages containing educational messages related to bullying and local cultural. The research method is Research and Development (R&D) with the 4D development model (Define, Design, Develop, Disseminate). The data collection techniques used in this study were observation, interviews, and questionnaires. The data obtained was then analyzed using quantitative descriptive analysis techniques, namely the results of the bilingual audio e-comic validity test. The product validity assessment was carried out by media experts and material experts or the content of the story. The material expert's score obtained a score of 95.64%, which means that e-comic is very valid for use. The media expert validation is 100%, which means that e-comic is very valid to use. Based on the results of the study, it can be concluded that the e-comic with audio in Indonesian and Javanese meets the eligibility standards for use in elementary school students. The product is very feasible to use as educational media for anti- bullying and local culture in elementary school students.